Community Involvement and Narrative Identity in Emerging and Young Adulthood: A Longitudinal Analysis. Issue 1 (2nd January 2017) - Hasford, Julian; Abbott, Kayleigh; Alisat, Susan; Pancer, S. Mark; Pratt, Michael W.
ABSTRACT: This study examines community engagement in youth and emerging adulthood from a narrative identity perspective, based on analyses of a longitudinal data set of 72 participants from ages 17 to 32. At ages 26 and 32, participants told narratives about a key community experience from their personal lives, which was rated for six dimensions. In addition, questionnaire measures of community involvement and general identity status development were administered at ages 17, 26, and 32. We found that patterns of community involvement at age 17 predicted levels of community involvement and qualities of community narratives at ages 26 and 32 and that community narratives were significantly correlated with concurrent measures of identity maturity and community involvement. Limitations and implications for future research are discussed.